PENGARUH JUMLAH ANGGOTA DAN JUMLAH MODAL TERHADAP SISA HASIL USAHA KOPERASI SIMPAN PINJAM BALO’ TORAJA CABANG RANTEPAO KABUPATEN TORAJA UTARA - Rati Pundissing; Westerini Lusdani; Sussana Eka Topayung (Widya Amerta, 2023)
This study aims to determine whether the number of members and the amount of capital affect the remaining results of operations at the Balo' Toraja Savings and Loan Cooperative, Rantepao Branch. This type of research is quantitative research, namely data in the form of numbers and can be calculated using multiple linear regression methods using SPSS. The type of data used in this study is primary data taken from questionnaire data. The data collected is directly sourced from the Rantepao Branch of the Balo'ta Savings and Loans Cooperative Office. The sampling technique used the slovin technique with a population of 2,713 cooperative members with a sample of 78 people as respondents. The data collection method is a questionnaire. Based on the research results, it was found that the number of members did not have a positive effect on the remaining results of operations, while the amount of capital had a positive and significant effect on the remaining results of operations. And the number of members and the amount of capital simultaneously affect the remaining results of operations at the Balo' Toraja Savings and Loans Cooperative, Rantepao Branch, North Toraja Regency.